Protecting medical staff from skin injury/disease caused by personal protective equipment during epidemic period of COVID‐19: experience from China - Long, H.; Zhao, H.; Chen, A.; Yao, Z.; Cheng, B.; Lu, Q. (Journal of the European Academy of Dermatology and Venereology, 2020)
Linked articles: COVID‐19 SPECIAL FORUM. J Eur Acad Dermatol Venereol 2020; 34: e210–e216.